2010
DOI: 10.1111/j.1460-9568.2010.07114.x
|View full text |Cite
|
Sign up to set email alerts
|

Incubation of nicotine seeking is associated with enhanced protein kinase A‐regulated signaling of dopamine‐ and cAMP‐regulated phosphoprotein of 32 kDa in the insular cortex

Abstract: A recent clinical study demonstrated that damage to the insular cortex can disrupt tobacco addiction. The neurobiological mechanisms for this effect are not yet understood. In this study we used an animal model of nicotine addiction to examine the possibility that changes in insular cortex levels of dopamine (DA)- and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32), a phosphoprotein enriched in DA neurons containing DA D1 receptors, may be associated with changes in vulnerability to nicotine addiction. Once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 42 publications
5
92
2
Order By: Relevance
“…Results from two studies showed that the response to smokingassociated cues in humans and to nicotine-associated cues in rats progressively increases or incubates after withdrawal (Abdolahi et al, 2010;Bedi et al, 2011). In the human study, Bedi et al (2011) showed that nicotine-cue-induced subjective craving is higher after 35 withdrawal days than after 7 or 14 d. In the rat study, Abdolahi et al (2010) showed that, after nicotine selfadministration, extinction responding and subsequent cueinduced reinstatement after extinction are higher after 7 withdrawal days than after 1 d. The results of Abdolahi et al (2010) extend previous rat studies on "incubation of drug craving" after withdrawal from cocaine (Neisewander et al, 2000;Grimm et al, 2001), heroin (Shalev et al, 2001), methamphetamine (Shepard et al, 2004), or alcohol (Bienkowski et al, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Results from two studies showed that the response to smokingassociated cues in humans and to nicotine-associated cues in rats progressively increases or incubates after withdrawal (Abdolahi et al, 2010;Bedi et al, 2011). In the human study, Bedi et al (2011) showed that nicotine-cue-induced subjective craving is higher after 35 withdrawal days than after 7 or 14 d. In the rat study, Abdolahi et al (2010) showed that, after nicotine selfadministration, extinction responding and subsequent cueinduced reinstatement after extinction are higher after 7 withdrawal days than after 1 d. The results of Abdolahi et al (2010) extend previous rat studies on "incubation of drug craving" after withdrawal from cocaine (Neisewander et al, 2000;Grimm et al, 2001), heroin (Shalev et al, 2001), methamphetamine (Shepard et al, 2004), or alcohol (Bienkowski et al, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…An analogous phenomenon, termed 'incubation of drug craving', was subsequently identified in rats, based on observations that time-dependent increases in cue-induced cocaine or heroin seeking occurred after withdrawal from these drugs (Grimm et al, 2001;Neisewander et al, 2000;Shalev et al, 2001). Subsequent studies have demonstrated that incubation of drug craving also occurs in rats with a history of nicotine, alcohol, or methamphetamine self-administration (Abdolahi et al, 2010;Bienkowski et al, 2004;Shepard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In rats, drug seeking progressively increases after forced abstinence from cocaine (Tran-Nguyen et al, 1998;Grimm et al, 2001), heroin (Shalev et al, 2001), nicotine (Abdolahi et al, 2010), alcohol (Bienkowski et al, 2004), and methamphetamine self-administration, a phenomenon termed "incubation of drug craving" (Lu et al, 2004). These studies inspired clinical studies demonstrating the incubation of nicotine (Bedi et al, 2011), alcohol , cocaine (Parvaz et al, 2016), and methamphetamine (Wang et al, 2013) craving in humans.…”
Section: Introductionmentioning
confidence: 99%